Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12872-017-0620-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for coronary artery disease in patients undergoing elective coronary angiography in Jordan

Abstract: BackgroundUnhealthy lifestyle factors such as smoking, obesity, inactivity and type 2 diabetes are endemic in the Middle East. The public health consequences might be detrimental; however, local studies on risk factors for coronary artery disease (CAD) are scarce.MethodsPatients referred for coronary angiography at a tertiary hospital in Amman, Jordan, between January and December 2015, were included in this study. Risk factors for CAD were assessed in a multivariate logistic regression model, and presented as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 16 publications
(14 reference statements)
4
19
0
Order By: Relevance
“…In some studies, low and moderate consumption of alcohol was found to be a protective factor for CAD, 17 but we found discrepant results because we did not categorize alcohol use as heavy or moderate. In addition to these two variables, as in most other studies, 4,22 occupation, diabetes mellitus, dyslipidaemia, obesity, family income, family history, physical activity, mental illness, and sleep disturbance were found to be significantly associated with CAD. In this study, there was a high prevalence of current smokers (39.2%) and ex-smokers (23.9%) presenting CAD.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In some studies, low and moderate consumption of alcohol was found to be a protective factor for CAD, 17 but we found discrepant results because we did not categorize alcohol use as heavy or moderate. In addition to these two variables, as in most other studies, 4,22 occupation, diabetes mellitus, dyslipidaemia, obesity, family income, family history, physical activity, mental illness, and sleep disturbance were found to be significantly associated with CAD. In this study, there was a high prevalence of current smokers (39.2%) and ex-smokers (23.9%) presenting CAD.…”
Section: Discussionsupporting
confidence: 64%
“…36 In one study of non-smokers and current or previous smokers in Jordan, 56.7% of CAD patients were smokers and smoking doubled the risk of CAD compared to not smoking. 22 A significant association of past-year smoking was with CAD reported from patients hospitalized with coronary artery disease in an American population. 37 In a recent study among the Han population in China, gene-environment interactions between rs4886605 and smoking increased the risk of CAD.…”
Section: Discussionmentioning
confidence: 98%
“…According to our results, smoking, HTN, DM, and dyslipidemia were all significantly more prevalent in CAD-AF patients. This is consistent with most regional studies about CAD risk factors [21][22][23]. In a study conducted in Iraq on patients undergoing coronary angiography for CAD, being a male, smoking, hypertension, hyperlipidemia, and a family history of CAD were all linked with premature CAD [21].…”
Section: Discussionsupporting
confidence: 85%
“…In a study conducted in Iraq on patients undergoing coronary angiography for CAD, being a male, smoking, hypertension, hyperlipidemia, and a family history of CAD were all linked with premature CAD [21]. Another similar study in Jordan found that DM and smoking were associated with CAD, although they did not find any significant association between HTN or dyslipidemia with CAD [22]. Alsaud et al found that most patients with CAD in Jordan have a cluster of more than one cardiac risk factor [23].…”
Section: Discussionmentioning
confidence: 96%
“…During the last 30 years, people in Jordan have experienced behavioral and lifestyle changes 3. These changes have led to a rise in the prevalence of all types of diabetes in Jordan and also an increase in the risk factors associated with diabetes such as poor quality nutrition, more consumption of fast food, low intake of fruits and vegetables, reduced physical activity, obesity, smoking and poor awareness of healthy weight among people in Jordan 35. Additionally, inviting guests for sharing meals which include high-calorie content is considered as a highly valued socio-cultural habit in the Arab World and may contribute to the high prevalence of diabetes in Jordan 3.…”
Section: Introductionmentioning
confidence: 99%